The Effect of Cultural Competence Training on Empathy of Medical Residents - Zohreh Sohrabi; Atefeh Zabihi Zazoly; Somayeh Alizadeh; Azam Norouzi; Ghobad Ramezani; Akram Zhianifard (Kerman University of Medical Sciences, 2022)
Background: Cultural competence is a core skill for the healthcare team that reputable medical organizations and associations have always emphasized. Its components are essential in reducing health inequalities, increasing patient satisfaction, and improving health outcomes.Objectives: Considering that competency improvement will affect other skills and abilities, this study attempted to identify the effect of cultural competence training on the medical residents' empathy.Methods: This quasi-experimental study was conducted among 44 medical residents randomly divided into two groups (control and experimental). The participants were from various medical disciplines (internal medicine, pediatrics, psychiatry, surgery, pathology, and anesthesia). Cultural Competence was taught to the experimental group in a workshop. Then they were sent short educational messages based on the elements of the cultural competence model of Campinha-Bacote for a month. Data were collected using Jefferson's empathy questionnaire and analyzed using SPSS16.Results: In this study, forty-four residents were randomly divided into two groups of 22 people. There was no significant difference between the scores of participants in the two groups before the cultural competency course (P>0.05). However, there was a substantial difference between the scores of the two groups after the intervention (P<0.05). The empathy score was higher in the intervention group.Conclusion: According to the current study, cultural competence training enhances learners' empathy in clinical settings. It is recommended to be integrated into educational planning and new revisions of curriculums.